Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.5194/amt-3-1683-2010
|View full text |Cite
|
Sign up to set email alerts
|

Water droplet calibration of the Cloud Droplet Probe (CDP) and in-flight performance in liquid, ice and mixed-phase clouds during ARCPAC

Abstract: Abstract. Laboratory calibrations of the Cloud DropletProbe (CDP) sample area and droplet sizing are performed using water droplets of known size, generated at a known rate. Although calibrations with PSL and glass beads were consistent with theoretical instrument response, liquid water droplet calibrations were not, and necessitated a 2 µm shift in the manufacturer's calibration. We show that much of this response shift may be attributable to a misalignment of the optics relative to the axis of the laser beam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
366
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 366 publications
(396 citation statements)
references
References 44 publications
13
366
1
Order By: Relevance
“…The thin red and black lines show the impact of moving the sample/laser intersect point or sample volume along the laser axis or laterally in a direction perpendicular to the laser axis. The 1-sigma offsets are estimates of the variation from nominal for a typical instrument and are based observed offsets of FAAM's PCASP after realignments, measurements of a number of CDPs by the manufacturer (Baumgardner, 2012) and measurements by Lance et al (2010).…”
Section: Results and Impact Upon The Fennec Datasetmentioning
confidence: 99%
See 4 more Smart Citations
“…The thin red and black lines show the impact of moving the sample/laser intersect point or sample volume along the laser axis or laterally in a direction perpendicular to the laser axis. The 1-sigma offsets are estimates of the variation from nominal for a typical instrument and are based observed offsets of FAAM's PCASP after realignments, measurements of a number of CDPs by the manufacturer (Baumgardner, 2012) and measurements by Lance et al (2010).…”
Section: Results and Impact Upon The Fennec Datasetmentioning
confidence: 99%
“…Multiplying the sample area by the speed of the airflow through the laser and the measurement time interval provides a sample volume allowing a concentration to be measured. Lance et al (2010) showed that the CDP sample area can be measured using a droplet gun on a micro-positioning system. It should be noted, however, that due to the method used to define the sample area, described in Sect.…”
Section: Further Measurement Uncertaintiesmentioning
confidence: 99%
See 3 more Smart Citations